2022
DOI: 10.1186/s13567-022-01055-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of excretory and secretory proteins from Haemonchus contortus inducing a Th9 immune response in goats

Abstract: Th9 cells have been shown to play crucial roles in anti-parasite immunity, pathogenic microbe infection, and allergy. Previous studies have demonstrated that Haemonchus contortus excretory and secretory proteins (HcESPs) induce the proliferation of Th9 cells and alter the transcriptional level of IL-9 as well as its related pathways in the Th9 immune response after infection. However, the exact molecule(s) in HcESPs inducing the Th9 immune response is not yet known. In this study, flow cytometry, co-immunoprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Total Th9 cells in goat PBMCs were sorted by the flow-sorting cytometry method as described elsewhere [ 15 ]. Briefly, PBMCs were cultured in RPMI-1640 media containing rHcL6 for 2 h at 37 °C in a humidified 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total Th9 cells in goat PBMCs were sorted by the flow-sorting cytometry method as described elsewhere [ 15 ]. Briefly, PBMCs were cultured in RPMI-1640 media containing rHcL6 for 2 h at 37 °C in a humidified 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, 218 H. contortus excretory-secretory proteins (HcESPs) interacting with goat Th9 cells were identified by liquid chromatography-tandem mass spectrometry (LC‒MS/MS) analysis. H. contortus ribosomal protein L6 domain DE-containing protein (HcL6) was detected among the proteins interacting with Th9 cells [ 15 ]. Research should be conducted to identify the molecules that directly or indirectly regulate Th9 cells at the parasite-host interface.…”
Section: Introductionmentioning
confidence: 99%
“…In the near future, controlling some parasites with current anthelminthic medications like oxfendazole, levamisole, and ivermectin may become more challenging ( 10 ). H. contortus has evolved different strategies to evade host immune response during infection ( 12 , 13 ). Parasitic nematodes cause a long-term infection in the host, generally with just a modest inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…The proteomic analysis of glycoproteins of H. contortus showed that 43 proteins were identified in the adult stage, and 34 and 35 proteins were bound by Lectin galacto side-binding soluble (LGALS)-11 and LGALS-14, respectively ( Sakthivel et al., 2018 ). Shotgun LC−MS/MS was used to identify 218 H. contortu s excretory and secretory proteins Haemonchus contortus Excrete Secretion Proteins (HcESPs) that interact with goat Th9 cells, which provides a new way to explore immunostimulatory antigens among HcESPs of H. contortus infection ( Liang et al., 2022 ). Subsequently, iTRAQ-coupled LC−MS/MS was also applied to analyze the differentially expressed proteins (DEPs) in adult parasites between water buffalo and yellow cattle, and 131 DEPs were identified, including 46 upregulated proteins and 85 downregulated proteins ( He et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%